Pengaruh Gaya Kepemimpinan dan Komitmen Organisasi Terhadap Efektivitas Kerja (Studi Pada Karyawan PT. Sing Wealth Textiles Ligung Majalengka) - Endah Prihartini (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
Abstract. Work effectiveness of employees of PT. Sing Wealth Textile has a problem, namely not achieving the target that has been determined and given by the manager to the employees. one of the factors to increase work effectiveness is through leadership style and organizational commitment. Leadership style and organizational commitment are considered as one of the factors that can affect work effectiveness. This study aims to determine how the influence of leadership style and organizational commitment partially on the work effectiveness of the study on employees of PT. Sing Wealth Textiles. This research is a survey research using a descriptive and verification approach. The population in this study were all employees of PT. Sing Wealth Textiles with a total sample of 81 respondents. The sampling technique used is simple random sampling. The data collection technique in this study was distributing questionnaires using a likert scale. Data analysis using classical assumption test, multiple regression analysis, coefficient of determination, model feasibility test and hypothesis testing using partial test. The results showed that leadership style and organizational commitment partially have a positive and significant effect on work effectiveness.